Implementasi Pembelajaran Sains pada Anak melalui Kegiatan Menanam Sayur Kangkung Hidroponik - Indahwati, Mamik; AR, Zaini Tamin (Program Studi Pendidikan Islam Anak Usia Dini STAI YPBWI Surabaya, 2021)
One of the factors that causes the lack of development of children's science skills is monotonous learning. Teachers are more likely to provide explanations and assignments. So, even though science has been taught, children do not understand it well. This study aims to determine the implementation of children's science learning through hydroponic kangkung planting activities at Mutiara Ummi Baby School and Child Care, Candi District, Sidoarjo Regency. This study uses a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. This study found that more than 50% of students have very well developed science skills, because students are able to do it independently and have been able to help their friends who have not achieved their abilities based on assessment indicators. Therefore, these activities need to be applied as a variation of science learning in children. To be more optimal, institutions must provide a variety of complete and adequate infrastructure.